Integration of James banks' multicultural theory in mathematics learning - Wewe, Melkior; I Wayan Suastra; Ananta Wikrama Tungga Atmaja; I Nyoman Tika (Universitas Islam Negeri Raden Intan Lampung, 2025)
Multicultural education and ethnomathematics share a philosophical orientation that positions education as a process of humanization and cultural empowerment. Integrating these perspectives offers a broader foundation for culturally responsive mathematics education. This study aims to formulate an integrative conceptual framework that synthesizes James A. Banks’ multicultural education theory with D’Ambrosio’s ethnomathematics principles to guide equitable and culturally grounded mathematics instruction. A Systematic Literature Review (SLR) was conducted using thematic analysis and theoretical synthesis of 20 peer-reviewed articles and six foundational academic books published between 2015 and 2025. The analytical procedure employed open coding, axial coding, and selective coding to identify theoretical convergences across the two frameworks. The study proposes the 3E Framework: Equity, Engagement, and Empowerment, conceptualizing mathematics learning as a culturally situated, reflective, and empowering process. Multicultural ethnomathematics-based instruction enhances students’ multicultural awareness, strengthens connections between mathematical concepts and local cultural practices, and fosters higher-order thinking skills. This framework contributes to the development of humanistic and inclusive mathematics pedagogy aligned with Indonesia’s Merdeka Belajar policy and the Profil Pelajar Pancasila framework. Although conceptual, the model provides a foundation for future empirical validation to assess its effectiveness in classroom practice.